Emulsification Increases the Acute Ketogenic Effect and Bioavailability of Medium-Chain Triglycerides in Humans: Protein, Carbohydrate, and Fat Metabolism. Issue 7 (21st June 2017) - Courchesne-Loyer, Alexandre; Lowry, Carolyn-Mary; St-Pierre, Valérie; Vandenberghe, Camille; Fortier, Mélanie; Castellano, Christian-Alexandre; Wagner, J Richard; Cunnane, Stephen C
Abstract: Background: Lower-brain glucose uptake is commonly present before the onset of cognitive deterioration associated with aging and may increase the risk of Alzheimer disease. Ketones are the brain's main alternative energy substrate to glucose. Medium-chain triglycerides (MCTs) are rapidly β-oxidized and are ketogenic but also have gastrointestinal side effects. We assessed whether MCT emulsification into a lactose-free skim-milk matrix [emulsified MCTs (MCT-Es)] would improve ketogenesis, reduce side effects, or both compared with the same oral dose of MCTs consumed without emulsification [nonemulsified MCTs (MCT-NEs)]. Objectives: Our aims were to show that, in healthy adults, MCT-Es will induce higher ketonemia and have fewer side effects than MCT-NEs and the effects of MCT-NEs and MCT-Es on ketogenesis and plasma medium-chain fatty acids (MCFAs) will be dose-dependent. Methods: Using a metabolic study day protocol, 10 healthy adults were each given 3 separate doses (10, 20, or 30 g) of MCT-NEs or MCT-Es with a standard breakfast or no treatment [control (CTL)]. Blood samples were taken every 30 min for 4 h to measure plasma ketones (β-hydroxybutyrate and acetoacetate), octanoate, decanoate, and other metabolites. Participants completed a side-effects questionnaire at the end of each study day. Results: Compared with CTL, MCT-NEs increased ketogenesis by 2-fold with no significant differences between doses. MCT-Es increased total plasma ketones by 2- to 4-fold in a dose-dependent manner. Compared with MCT-NEs, MCT-Es increased plasma MCFA bioavailability ( F ) by 2- to 3-fold and decreased the number of side effects by ∼50%. Conclusions: Emulsification increased the ketogenic effect and decreased side effects in a dose-dependent manner for single doses of MCTs ≤30 g under matching conditions. Further investigation is needed to establish whether emulsification could sustain ketogenesis and minimize side effects and therefore be used as a treatment to change brain ketone availability over a prolonged period of time. This trial was registered at clinicaltrials.gov as NCT02409927.